2003
DOI: 10.1103/physrevb.68.193203
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the spin-charge thermal isolation of ferromagneticGa0.94Mn0.06Asby time-resolved magneto-optica

Abstract: The dynamics of magnetization under femtosecond optical excitation is studied in a ferromagnetic semiconductor Ga 0.94 Mn 0.06 As with a time-resolved magneto-optical Kerr effect measurement with two color probe beams. The transient reflectivity change indicates the rapid rise of the carrier temperature and relaxation to a quasi-thermal equilibrium within a few ps, while a very slow rise of the spin temperature of the order of 500ps is observed. This anomalous behavior originates from the thermal isolation bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
59
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 26 publications
8
59
0
Order By: Relevance
“…A different process with a similar relaxation time ∼ 1ps has been observed previously, and has been attributed to trapping of photoexcited electrons by crystal defects, with no relation to the magnetic system [38][39][40] . Our present results thus point to a need for future studies aimed at a better understanding of the hole-energy dynamics occurring in ferromagnetic semiconductors.…”
Section: A Short-time Dynamics: Hole Spin and Energy Relaxationmentioning
confidence: 75%
“…A different process with a similar relaxation time ∼ 1ps has been observed previously, and has been attributed to trapping of photoexcited electrons by crystal defects, with no relation to the magnetic system [38][39][40] . Our present results thus point to a need for future studies aimed at a better understanding of the hole-energy dynamics occurring in ferromagnetic semiconductors.…”
Section: A Short-time Dynamics: Hole Spin and Energy Relaxationmentioning
confidence: 75%
“…(2) in [17]). The former reflects the pump-induced change of the sample magnetization and the latter is connected with the pump-induced change of the electronic properties of the sample [17]. Recently, we have showed that the oscillatory part of the signal is very similar in the Kerr rotation and ellipticity measurements (see Fig.…”
mentioning
confidence: 99%
“…© 2007 American Institute of Physics. ͓DOI: 10.1063/1.2719173͔ Current research activities in the area of ferromagnetic semiconductor have been mainly focused on III-Mn-V alloys with small lattice constants and large effective masses of valence band such as GaMnAs, [1][2][3][4] where the highest values of the Curie temperature ͑T C ͒ have been achieved so far. Various theoretical models have been proposed to explain the actual mechanism of ferromagnetism in III-Mn-V but the microscopic mechanism is still a matter of controversy.…”
mentioning
confidence: 99%